Production of formic acid from CO2 reduction by means of potassium borohydride at ambient conditions. (1st December 2015) - Fletcher, Cameron; Jiang, Yijiao; Amal, Rose
Abstract: The present study provides an efficient process for the high-yield production of formic acid (24%) by reduction of carbon dioxide (CO2 ) with potassium borohydride at ambient conditions. The effects of reaction temperature, CO2 pressure and borohydride concentration have been investigated. For a 0.5 M borohydride solution, 0.15 mol/L of formic acid were produced at room temperature and ambient pressure with yields increasing at higher pressures. A time-resolved in situ 1 H and 11 B nuclear magnetic resonance (NMR) technique was firstly developed to monitor the elementary reaction processes under real working conditions. Direct evidence is given for the formation of H2, HD and a hydroxyborohydride intermediate (BH3 OH − ) formed during borohydride decomposition indicating that the source of the hydrogen gas comes from both the borohydride anion and water, while borohydride works as a water-splitting reagent. Consequently, a reaction mechanism involved in both borohydride hydrolysis and CO2 reduction has been established. Highlights: High-yield production of formic acid by reduction of CO2 at ambient conditions. 0.15 /L of formic acid were produced by using 0.5 M borohydride solution. Time-resolved in situ NMR was firstly developed to understand the process. A reaction mechanism involved in CO2 reduction and BH4 − hydrolysis was established.